Conductive paste composition for internal electrodes of multilayer ceramic capacitors, method for producing the same, and conductive paste
By adjusting the average particle size ratio and content of conductive powder and ceramic powder, the problems of oversintering and electrode discontinuity of conductive powders such as small-particle nickel powder are solved, the continuity and coverage of the internal electrode layer are improved, and the miniaturization and large-capacity of the laminated ceramic capacitors are promoted.
Patent Information
- Application Number
- CN202080076238.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-10-31
- Filing Date
- 2020-06-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2040-06-23
AI Technical Summary
When a metal powder such as a small particle size nickel powder is used as the conductive powder, it is difficult to suppress oversintering of the conductive powder and electrode interruption, resulting in discontinuity of the internal electrode layer and poor short circuit.
By adjusting the average particle size ratio and content of the conductive powder and the ceramic powder, the average particle size of the conductive powder is specifically controlled to be 0.12 μm or more and 0.3 μm or less, the average particle size ratio of the ceramic powder is controlled to be 0.1 or more and less than 0.3, and the content of the ceramic powder is adjusted to be 5.5% or more and 13% or less, so as to suppress oversintering of the conductive powder.
It effectively suppresses oversintering of conductive powder and electrode interruption, improves the coverage of the internal electrode layer after sintering, further miniaturizes and large-capacity of stacked ceramic capacitors, and improves the life and reliability of the product.
Smart Images

Figure CN114641835B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive paste composition for forming an internal electrode of a laminated ceramic capacitor, a method for producing the same, and a conductive paste using the composition. Background Art
[0002] Multilayer ceramic capacitors (MLCCs) are chip-type ceramic capacitors made by stacking a large number of dielectric layers and electrode layers made of titanium oxide (TiO2) or barium titanate (BaTiO3). Multilayer ceramic capacitors are used in a wide range of electronic circuits because they can fully utilize the advantages of ceramics such as excellent high-frequency characteristics and can be small and large in capacity. In particular, large-capacity multilayer ceramic capacitors are used in a wide range of applications such as bypass, decoupling, smoothing, and backup.
[0003] Laminated ceramic capacitors are usually manufactured as follows. First, in order to form a ceramic dielectric layer, a conductive paste made by dispersing a conductive powder composed of a metal powder such as nickel powder in a carrier containing a resin binder and a solvent is printed in a predetermined pattern on a dielectric raw sheet composed of a dielectric powder composed of a ceramic powder and an organic binder such as polyvinyl butyral, and the solvent is removed by drying to form a dry film. Next, the dielectric raw sheet printed with the conductive paste is heat-pressed in a multi-layer stacked state, and the dielectric layer and the internal electrode layer are integrated and then cut, and the binder is removed at a temperature below 500°C in an oxidizing environment or an inactive environment. Then, in order to prevent the internal electrode from oxidizing, the laminate is heated and fired at a temperature of about 1300°C in a reducing environment. Furthermore, a metal paste as an external bridge is applied to the obtained fired chip, and after firing, two layers of nickel and tin plating are performed on the external electrode, thereby completing the laminated ceramic capacitor.
[0004] In recent years, there is a demand for further miniaturization and higher capacity of multilayer ceramic capacitors. For example, for internal electrodes made of nickel, thinning of electrode films with excellent continuity is being studied, and for dielectric layers made of ceramic dielectric materials, higher dielectric constants and thinner layers are being studied. For dielectric layers, a thickness of 2.0 μm or less has been achieved. For electrode films, it is expected that the thickness is 1.0 μm or less.
[0005] In order to achieve thinning of the electrode films constituting such internal electrodes, metal powders such as nickel powders having a small particle size have been used as conductive powders for conductive pastes in recent years.
[0006] Compared with the ceramic powder constituting the green sheet, the metal powder has a lower melting point and changes into a dense electrode film while shrinking during the firing process. In contrast, the melting point of the ceramic powder is higher than that of the metal powder. After the metal powder is sintered, the ceramic powder shrinks during sintering. Therefore, the electrode film is easily peeled off from the dielectric layer, resulting in the discontinuity of the electrode film.
[0007] In order to eliminate the inconsistency in the sintering temperature, a method is adopted in which a dielectric powder called a co-material, which is the same as the dielectric powder used for the green sheet, is added to the internal electrode paste.
[0008] This suppresses contact between metal powders in the conductive paste, and can delay sintering of the metal powders.
[0009] For example, when nickel powder is used as a conductive powder, as the multilayer ceramic capacitor is miniaturized, nickel powder with an average particle size of 0.2 μm is used instead of the conventional nickel powder with an average particle size of 0.4 μm. As the particle size of the nickel powder is reduced, it is increasingly difficult to control the sintering delay using the same material.
[0010] That is, nickel powder with a small particle size tends to start sintering faster. Therefore, during the sintering stage, the sintered nickel particles lose the connection between them, and after sintering, they are easily over-sintered in an isolated island state. If such an over-sintered state occurs, the film breakage of the internal electrode layer increases, the area of the internal electrode is reduced, the electrostatic capacitance becomes low, or in the worst case, the electrostatic capacitance is completely not obtained, resulting in a significant deterioration in the yield of the product.
[0011] In addition, from the viewpoint of suppressing short-circuit failures of multilayer ceramic capacitors that are prone to occur as the layers become thinner, the surface roughness of the internal electrode layers is required to be reduced. As the particle size of the conductive powder becomes smaller, the particle size of the dielectric powder as a common material also tends to become smaller.
[0012] If the dielectric powder as a common material is reduced in particle size, the sintering start temperature of the common material itself is lowered. In this way, if the common material with a small particle size is sintered at a lower sintering temperature, the effect of suppressing the sintering of nickel powder brought by the common material disappears. As a result, since the contact barrier effect between the conductive powders disappears at a lower temperature, the sintering of the conductive powder is promoted at a lower temperature, and the continuity of the internal electrode layer disappears.
[0013] Therefore, even when a metal powder such as nickel powder having a small particle size is used as the conductive powder, a method for suppressing and controlling sintering of the conductive powders and suppressing discontinuity of the internal electrode layer is required.
[0014] In contrast, for example, in Japanese Patent Publication No. 57-030308, a dielectric powder as a common material is pre-adsorbed on the surface of a base metal powder and dispersed in an organic carrier, thereby suppressing the abnormal grain growth of the base metal powder during firing, thereby forming a dense and stable electrode without pores.
[0015] In addition, in Japanese Patent Gazette No. 2016-033962, from the viewpoint of ensuring the continuity of internal electrodes, suppressing the deviation of electrostatic capacitance and reducing dielectric loss, a conductive paste is disclosed, which is a conductive paste containing ceramic powder, conductive powder and binder resin, and has a conductive powder with an average particle size of 0.1μm to 0.4μm obtained by calculating the specific surface area according to the BET method and a ceramic powder with an average particle size of 0.01μm to 0.1μm obtained by calculating the specific surface area according to the BET method. When a stacked body formed by stacking raw sheets containing ceramic powder for raw sheets and binder resin with conductive paste printed on the surface is fired, as a firing condition, the temperature rise gradient after the debinding firing process to the maximum firing temperature and the amount of ceramic powder added relative to 100 parts by weight of nickel powder have a specific relationship. Specifically, a conductive paste is disclosed, comprising 100 parts by weight of nickel powder having an average particle size of 0.2 μm and, depending on its relationship with the temperature rise gradient, any amount of barium titanate powder having an average particle size of 0.06 μm in a range of 5 to 25 parts by weight.
[0016] Prior art literature
[0017] Patent Literature
[0018] Patent document 1: Japanese Patent Application Publication No. 57-030308;
[0019] Patent document 2: Japanese Patent Application Publication No. 2016-033962. Summary of the invention
[0020] Problem that the invention aims to solve
[0021] However, the method described in Japanese Patent Application Laid-Open No. 57-030308 is difficult to apply to metal powders such as nickel powders with small particle sizes.
[0022] Japanese Patent Application Laid-Open No. 2016-033962 discloses the range of average particle sizes to which conductive powder and ceramic powder can be applied, but does not specifically propose a relationship between the average particle size of the conductive powder and the average particle size of the ceramic powder.
[0023] In addition, Japanese Patent Gazette No. 2016-033962 records that in the conductive paste, the specific surface area is calculated according to the BET method, and the average particle size of the conductive powder and the ceramic powder is calculated. Here, in the mixing and dispersing process of the conductive powder and the ceramic powder when making the conductive paste composition, the ceramic powder is first dispersed, and then the conductive powder and the dispersed ceramic powder are mixed and dispersed. This is because: since the particle size of the ceramic powder is small, if it is mixed with the conductive powder from the beginning, and mixed and dispersed, the ceramic powder is insufficiently dispersed, and the agglomerates of the ceramic powder exist in the internal electrode layer, which may cause short circuit defects in the stacked ceramic capacitor.
[0024] In the dispersion treatment, mechanical crushing is performed using a bead mill or the like, and at this time, not only is the ceramic powder dispersed but also the ceramic powder is chipped or cracked.
[0025] In this case, the ceramic powder deviates from the desired specific surface area, that is, deviates from the desired average particle size. For the conductive powder with a specified average particle size, it is impossible to select a ceramic powder with an appropriate average particle size, and there is a possibility that a multilayer ceramic capacitor with desired characteristics cannot be obtained.
[0026] The object of the present invention is to provide a conductive paste composition and a conductive paste for internal electrodes of a multilayer ceramic capacitor, which can suppress over-sintering of the conductive paste and electrode discontinuity during sintering, and can improve the coverage of the internal electrode layer after sintering.
[0027] Means used to solve problems
[0028] The present inventors have intensively studied a method for improving the continuity of the internal electrode film when using nickel powder having a small particle size, and as a result, have obtained the following findings regarding the relationship between the particle size of the nickel powder and the particle size of the common material.
[0029] That is, the following insights were obtained: (1) as the average particle size of the conductive powder and the common material, the average particle size in the particle size distribution based on the number of equivalent diameters (Heywood diameters) obtained by image processing of scanning electron microscope (SEM) photography was used; (2) the ratio of the average particle size of the conductive powder to the average particle size of the common material was limited to a specified range; (3) the content ratio of the conductive powder and the common material was adjusted to a specified range, thereby, when the particle size of the conductive powder and the common material was reduced, the over-sintering of the conductive powder could be suppressed, and the electrode discontinuity during sintering could be suppressed, thereby improving the coverage after sintering. The inventors completed the present invention based on this insight.
[0030] A conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to one embodiment of the present invention is characterized in that it comprises a conductive powder and a ceramic powder, wherein the average particle size in the number-based particle size distribution of the conductive powder is 0.12 μm or more and 0.3 μm or less, the average particle size in the number-based particle size distribution of the conductive powder is the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM), the ratio of the average particle size in the number-based particle size distribution of the ceramic powder to the average particle size of the conductive powder is 0.1 or more and less than 0.3, the average particle size in the number-based particle size distribution of the ceramic powder is the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM), and the content of the ceramic powder is 5.5% by mass or more and 13% by mass or less relative to the total mass of the conductive powder and the ceramic powder.
[0031] The ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is preferably 0.15 or more and 0.25 or less.
[0032] The average particle size of the conductive powder is preferably 0.15 μm or more and 0.25 μm or less.
[0033] The average particle size of the ceramic powder is preferably 0.02 μm or more and 0.07 μm or less, and more preferably 0.03 μm or more and 0.05 μm or less.
[0034] The conductive powder is preferably at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof.
[0035] The ceramic powder is preferably composed of a ceramic powder containing a perovskite-type oxide as a main component.
[0036] A conductive paste for internal electrodes of a multilayer ceramic capacitor according to one embodiment of the present invention is characterized in that it comprises a conductive paste composition and an adhesive, wherein the conductive paste composition is composed of the conductive paste composition according to the one embodiment of the present invention, and the content of the conductive paste composition is greater than 40% by mass and less than 60% by mass relative to the total mass of the conductive paste.
[0037] A method for producing a conductive paste composition according to one embodiment of the present invention is characterized by comprising:
[0038] A process for preparing conductive powder;
[0039] A process for preparing ceramic powder;
[0040] A step of dispersing the ceramic powder; and
[0041] The conductive powder is mixed with the ceramic powder after the dispersion treatment and the dispersion treatment is carried out.
[0042] In the step of preparing the conductive powder, a conductive powder having an average particle size of 0.12 μm or more and 0.3 μm or less in a number-based particle size distribution of an area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM) is selected,
[0043] In the step of preparing the ceramic powder, a ceramic powder is selected in which the ratio of the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM) to the average particle size of the conductive powder is 0.1 or more and less than 0.3,
[0044] In the step of mixing and dispersing the conductive powder and the ceramic powder after the dispersion treatment, the content of the ceramic powder is 5.5 mass % or more and 13 mass % or less relative to the total mass of the conductive powder and the ceramic powder.
[0045] The average particle size of the ceramic powder is preferably set to 0.15 or more and 0.25 or less relative to the average particle size of the conductive powder.
[0046] The average particle size of the conductive powder is preferably set to 0.15 μm or more and 0.25 μm or less.
[0047] The average particle size of the ceramic powder is preferably 0.02 μm or more and 0.07 μm or less, and more preferably 0.03 μm or more and 0.05 μm or less.
[0048] As the conductive powder, it is preferable to use at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof.
[0049] As the ceramic powder, it is preferable to use a ceramic powder containing a perovskite type oxide as a main component.
[0050] Effects of the Invention
[0051] By using the conductive paste of one embodiment of the present invention, over-sintering of the conductive powder is suppressed during the manufacture of the multilayer ceramic capacitor, and electrode discontinuity during sintering is prevented, thereby increasing the coverage of the internal electrode layer after sintering. Therefore, compared with the case of using the conventional conductive paste, since the film thickness of the internal electrode layer can be made thinner, the multilayer ceramic capacitor can be further miniaturized and increased in capacity, and its product life and reliability can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 An image of the fired film obtained in Example 3 taken with a scanning electron microscope (SEM) is shown.
[0053] Figure 2 An image of the fired film obtained in Comparative Example 3 taken with a scanning electron microscope (SEM) is shown. DETAILED DESCRIPTION
[0054] 1. Conductive paste composition for internal electrodes of multilayer ceramic capacitors and method for producing the same
[0055] A first aspect of the present invention relates to a conductive paste composition for internal electrodes of a multilayer ceramic capacitor.
[0056] A conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to one embodiment of the present invention comprises a conductive powder and a ceramic powder, wherein the average particle size in the particle size distribution based on the number of the conductive powder is 0.12 μm or more and 0.3 μm or less, the average particle size in the particle size distribution based on the number of the conductive powder is the average particle size in the particle size distribution based on the number of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM), the ratio of the average particle size in the particle size distribution based on the number of the ceramic powder to the average particle size of the conductive powder is 0.1 or more and less than 0.3, the average particle size in the particle size distribution based on the number of the ceramic powder is the average particle size in the particle size distribution based on the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM), and the content of the ceramic powder is 5.5% by mass or more and 13% by mass or less relative to the total mass of the conductive powder and the ceramic powder.
[0057] [Conductive powder]
[0058] As the conductive powder in the conductive paste composition of this embodiment, at least one metal powder selected from Ni (nickel), Pd (palladium), Pt (platinum), Au (gold), Ag (silver), Cu (copper) and alloys containing them as main components can be used.
[0059] In particular, in the application of internal electrodes of multilayer ceramic capacitors, since they are fired simultaneously with dielectric green sheets, it is preferable to use Ni powder, alloy powder containing Ni as a main component, Pd powder, and alloy powder containing Pd as a main component. In particular, from the viewpoint of manufacturing cost, it is more preferable to use Ni powder and alloy powder containing Ni as a main component.
[0060] The conductive powder has an average particle size of 0.12 μm or more and 0.3 μm or less in a number-based particle size distribution of an area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM).
[0061] Specifically, a photograph of the conductive particles is taken using a scanning electron microscope (SEM), and for more than 1000 conductive powders in the SEM photograph, the size (area) of each conductive particle is measured using an image processing device, and the area circle equivalent diameter (Heywood diameter) of each conductive particle is calculated based on the measured value, and the area circle equivalent diameter of all the conductive particles is converted into a particle size distribution based on the number of particles, and the average particle size in the area circle equivalent diameter (Heywood diameter) of the conductive powder in the particle size distribution based on the number of particles is calculated based on the obtained result.
[0062] The reason for setting the average particle size of the conductive powder to be less than 0.3 μm is that when the average particle size of the conductive powder, especially Ni powder, is larger than 0.3 μm, it may contain coarse particles with a particle size larger than 1 μm due to agglomeration. Such coarse particles may hinder the smoothness of the dry film obtained from the conductive paste or the metal film after firing, thereby making it difficult to thin the internal electrode layer.
[0063] When the average particle size of the conductive powder is less than 0.12 μm, it is difficult to obtain the effect of controlling sintering of the conductive powder when firing a conductive paste obtained using the composition, and thus the continuity of the obtained internal electrode layer may be reduced.
[0064] From such a viewpoint, the average particle size of the conductive powder is more preferably 0.15 μm or more and 0.25 μm or less.
[0065] It should be noted that in the present embodiment, the method for producing the conductive powder containing Ni powder is not limited as long as it has the above-mentioned properties.
[0066] [Ratio of average particle size of ceramic powder to average particle size of conductive powder]
[0067] Ceramic powder is used to control the sintering behavior of conductive powders such as Ni powder. That is, when an electrode film is formed only from conductive powder, sintering proceeds rapidly, resulting in a phenomenon called electrode discontinuity. Therefore, by adding ceramic powder, the overall sintering can be delayed. However, since ceramic powder does not function as an electrode, it is preferred to use as little ceramic powder as possible to control the sintering of the conductive powder.
[0068] In the conductive paste composition for internal electrodes of a multilayer ceramic capacitor of the present embodiment, the ratio of the average particle size in the number-based particle size distribution of the ceramic powder to the average particle size of the conductive powder is controlled to be greater than 0.1 and less than 0.3, and the average particle size in the number-based particle size distribution of the ceramic powder is the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM).
[0069] For the ceramic powder, the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM) is determined in the same manner as for the conductive powder.
[0070] For ceramic powder, the average particle size of the ceramic powder is obtained based on the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of the scanning electron microscope (SEM), thereby suppressing the deviation between the desired average particle size and the actual average particle size, which is based on the deviation of the specific surface area caused by the notch or crack of the ceramic powder in the process of dispersing the ceramic powder. Therefore, the ratio of the average particle size of the ceramic powder to the average particle size of the conductive particles can be appropriately controlled, and the desired conductive paste composition and the conductive paste for the internal electrodes of the stacked ceramic capacitor can be obtained, which can construct a stacked ceramic capacitor with desired characteristics in one embodiment of the present invention.
[0071] It is believed that in order to prevent the conductive particles from contacting each other, it is more effective to have a lot of ceramic powder between the conductive particles. Therefore, if the amount is the same, the smaller the average particle size of the ceramic powder and the more the amount of ceramic powder, the better. However, when the ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is less than 0.1, the smaller the particle size of the ceramic powder, the more it will cause sintering under low temperature conditions. Therefore, the ceramic powder existing between the conductive particles is over-sintered, and its particle size becomes huge, so that it cannot exist between the conductive particles, and the controllability of the sintering behavior of the conductive particles is lost. In this way, the effect of delaying the sintering of the conductive powders with each other brought by the ceramic powder is reduced, the sintering of the conductive powder cannot be properly controlled, the sintering shrinkage behavior of the internal electrode layer and the dielectric layer (green sheet) does not match, and the internal electrode layer is composed of an electrode film with low continuity.
[0072] On the other hand, in the case of delaying the sintering of the ceramic powder, it is effective to use a ceramic powder with a particle size as large as possible. However, when the ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is 0.3 or more, the number of particles decreases if the amount is the same, so in order to increase the number of particles, the amount of ceramic powder needs to be increased. Therefore, if the amount of ceramic powder as a common material is too much, the film thickness of the electrode film after firing tends to become thinner, and it is difficult to obtain the continuity of the internal electrode film.
[0073] The ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is preferably in the range of 0.12 or more and less than 0.3, and more preferably in the range of 0.15 or more and 0.25 or less.
[0074] [Ceramic powder]
[0075] The ceramic powder in the conductive paste composition of the present embodiment is preferably composed of a ceramic powder having a perovskite oxide as a main component. Examples of the perovskite oxide include barium titanate (BaTiO3). Therefore, it is preferred to use a ceramic powder composed of barium titanate and a ceramic powder to which various additives are added to barium titanate.
[0076] Specifically, it is preferably the same composition or a similar composition as the ceramic powder used as the main component of the green sheet forming the dielectric layer of the laminated ceramic capacitor, and various ceramic powders can be applied accordingly. The ceramic powder of the green sheet and the ceramic powder in the conductive paste composition are preferably ceramic powders containing barium titanate as the main component.
[0077] The ceramic powder preferably has an average particle size of 0.02 μm or more and 0.07 μm or less in a number-based particle size distribution of an area circle equivalent diameter (Heywood diameter) obtained by image processing of an image taken with a scanning electron microscope (SEM).
[0078] The definition of the average particle size in the number-based particle size distribution of the area circle equivalent diameter (Heywood diameter) obtained by image processing of an image captured by a scanning electron microscope (SEM) is the same as that of the conductive powder.
[0079] When the average particle size of the ceramic powder is less than 0.02 μm, the effect of delaying the sintering of the conductive powder disappears under relatively low temperature conditions, and thus the continuity of the internal electrode layer is sometimes reduced. When the average particle size of the ceramic powder is greater than 0.07 μm, the following problems may occur: the surface roughness of the internal electrode layer deteriorates, resulting in a short circuit failure of the laminated ceramic capacitor, and the ceramic powder is difficult to enter between the contact points of the conductive powder, so that the desired dry film density cannot be obtained, and the effect of delaying the sintering start temperature of the conductive powder is reduced.
[0080] The average particle size of the ceramic powder is more preferably 0.03 μm or more and 0.05 μm or less.
[0081] In the present embodiment, as long as the ceramic powder has the above-mentioned characteristics, the manufacturing method thereof is not limited. Regarding the manufacturing method of the ceramic powder, there are various methods such as a solid phase method, a hydrothermal synthesis method, an alkoxide method, and a sol-gel method. However, among them, the ceramic powder obtained by the hydrothermal synthesis method has a fine and sharp particle size distribution, and therefore, is preferably used as the ceramic powder applicable to the present embodiment.
[0082] [Content of ceramic powder]
[0083] In the conductive paste composition of the present embodiment, the content of the ceramic powder is 5.5% by mass or more and 13% by mass or less relative to the total mass (100% by mass) of the conductive powder and the ceramic powder. It is preferably 7% by mass or more and 12.5% by mass or less, and more preferably 9% by mass or more and 12% by mass or less.
[0084] When the content of ceramic powder is less than 5.5% by mass, the sintering of the conductive powder cannot be controlled, and the continuity of the internal electrode layer is reduced. In addition, since the sintering shrinkage behavior of the internal electrode layer and the dielectric layer becomes significantly mismatched, the difference in sintering temperature between the internal electrode layer and the dielectric layer becomes large, and firing cracks may occur.
[0085] On the other hand, when the ceramic powder content is greater than 13% by mass, the diffusion of the ceramic powder constituting the conductive paste into the green sheet (dielectric layer) becomes greater, the effect of the ceramic powder on delaying the start of sintering of the conductive powder is reduced, and the continuity of the internal electrode layer is reduced. In addition, since the ceramic powder diffused from the internal electrode layer and the ceramic powder in the dielectric layer are sintered, the thickness of the dielectric layer expands and the composition deviates. Therefore, problems such as a decrease in the dielectric constant and other adverse effects on the electrical properties may occur.
[0086] [Method for producing conductive paste composition]
[0087] The method for manufacturing the conductive paste composition of this embodiment includes, as in the conventional method, a step of preparing conductive powder, a step of preparing ceramic powder, a step of dispersing the ceramic powder, and a step of mixing and dispersing the conductive powder with the dispersed ceramic powder.
[0088] In particular, in the manufacturing method of the conductive paste composition of the present embodiment, as described above, in the process of preparing the conductive powder, a conductive powder is selected whose average particle size in the particle size distribution based on the number basis of the area circle equivalent diameter (Heywood diameter) obtained by image processing of the scanning electron microscope (SEM) image is 0.12 μm or more and 0.3 μm or less, and in the process of preparing the ceramic powder, a ceramic powder is selected whose ratio of the average particle size in the particle size distribution based on the number basis of the area circle equivalent diameter (Heywood diameter) obtained by image processing of the scanning electron microscope (SEM) image to the average particle size of the conductive powder is 0.1 or more and less than 0.3.
[0089] In the step of mixing and dispersing the conductive powder and the ceramic powder after the dispersion treatment, the content of the ceramic powder is 5.5 mass % or more and 13 mass % or less relative to the total mass of the conductive powder and the ceramic powder.
[0090] The selection of each method and numerical value, the preferred embodiment and the preferred value including the reasons thereof are as described above, and therefore, the description thereof is omitted here.
[0091] 2. Conductive paste for internal electrodes of multilayer ceramic capacitors
[0092] A second aspect of the present invention relates to a conductive paste for internal electrodes of a multilayer ceramic capacitor.
[0093] A conductive paste for internal electrodes of a multilayer ceramic capacitor according to one embodiment of the present embodiment includes a conductive paste composition and a binder.
[0094] [Content of Conductive Paste Composition]
[0095] The conductive paste of this embodiment is characterized in that a conductive paste composition of one embodiment of the present invention is used as the conductive paste composition, and the content of the conductive paste composition is greater than 40 mass % and less than 60 mass % relative to the total mass of the conductive paste (100 mass %).
[0096] When the content of the conductive paste composition is less than 40% by mass, it is difficult to control the film thickness when printing the conductive paste. When the content of the conductive paste composition is more than 60% by mass, it is difficult to print a thin electrode film and thin the internal electrode layer.
[0097] [Adhesive]
[0098] As a binder used when the conductive paste composition is made into a paste, a known viscosity modifier such as an organic vehicle and an aqueous vehicle can be used.
[0099] As the resin constituting the organic vehicle, one or more kinds of organic resins selected from methyl cellulose, ethyl cellulose, nitro cellulose, acrylic acid, polyvinyl butyral, and the like can be used.
[0100] In addition, the amount of resin in the conductive paste is preferably 1.0% by mass or more and 8.0% by mass or less, and more preferably 2.0% by mass or more and 6.0% by mass or less. When the amount of resin in the conductive paste is less than 1.0% by mass, it is difficult to obtain a viscosity suitable for screen printing. When the amount of resin in the conductive paste is greater than 8.0% by mass, the amount of residual carbon increases when the binder is removed, which may cause delamination of the stacked chips.
[0101] The binder contains an organic solvent that dissolves the resin component. The organic solvent also has the function of stably dispersing the inorganic components composed of the conductive powder and the ceramic powder in the paste and uniformly spreading these powders when the conductive paste is applied or printed on the green sheet. The organic solvent escapes into the atmosphere before firing.
[0102] As such organic solvents, there are no limitations thereto, and terpineol (α, β, γ and mixtures thereof), dihydroterpineol, octanol, decanol, tridecanol, dibutyl phthalate, butyl acetate, butyl carbitol, butyl carbitol acetate, dipropylene glycol monomethyl ether and the like can be used.
[0103] When a water-based vehicle is used as the binder resin, polyvinyl alcohol, a cellulose-based resin, or a water-soluble acrylic resin can be used.
[0104] The conductive paste of the present embodiment is applied on the surface of the green sheet by screen printing, and is dried by heating to remove the organic solvent, thereby forming a dry film of a predetermined pattern.
[0105] The raw sheet usually has a thickness of more than 0.5μm and less than 3μm, and has BaTiO3 as a perovskite-type oxide as the main component, with the addition of known inorganic additives for improving dielectric properties and sintering properties, and is mixed with polyvinyl butyral resin as a binder resin and known plasticizers for maintaining flexibility, thereby being formed into a sheet.
[0106] The organic solvent of the conductive paste is removed during the process of heating and drying to form a dry film. The dry film and the green sheet are laminated in multiple layers and then heat-pressed to form an integrated laminate. The laminate is cut into the shape of a laminated ceramic capacitor, and during the firing process, the binder is removed by heat treatment in an oxidizing environment or an inactive environment at a maximum temperature of 800°C or less, preferably 300°C or less, while preventing oxidation of the internal electrodes and reducing the amount of residual carbon. After the binder removal process, the temperature is raised to a maximum temperature of 1150°C or more and 1300°C or less in an inactive environment or a reducing environment, and the conductive powder and ceramic powder of the dry film, and the ceramic powder of the green sheet are sintered respectively.
[0107] In this embodiment, the conductive powder and the ceramic powder are selected based on the average particle size in the particle size distribution based on the number of area circle equivalent diameters (Heywood diameters) obtained by image processing of a scanning electron microscope (SEM), and the ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is limited to an appropriate range, and the content of the ceramic powder suitable for the ratio is determined. Therefore, even in the case where the average particle size of the conductive powder is 0.3 μm or less, the ceramic powder whose average particle size is appropriately controlled relative to the average particle size of the conductive powder appropriately enters between the contacts of the conductive powder, and the effect of appropriately delaying the start of sintering of the conductive powder can be exerted. As a result, the surface roughness of the dry film can be reduced, and the over-sintering of the conductive paste during firing can be suppressed. In the electrode film after firing, the electrode discontinuity is fully suppressed, the coverage of the internal electrode layer is increased, and further, the effect of suppressing short circuit failure of the stacked ceramic capacitor is obtained.
[0108] Example
[0109] Hereinafter, one embodiment of the present invention will be described in more detail using examples, but the present invention is not limited to these examples.
[0110] [Example 1]
[0111] [Conductive powder]
[0112] As a conductive powder, Ni powder is used. For various Ni powders, a scanning electron microscope (SEM) (manufactured by JEOL Ltd., 6360A) is used to take pictures and obtain SEM images. According to these SEM images, after measuring the particle size of more than 1000 particles of each Ni powder using image analysis particle size distribution measurement software (manufactured by MOUNTECH Co., Ltd., Mac-View), for each Ni powder, the area circle equivalent diameter (Heywood diameter) is calculated to obtain the average particle size in the particle size distribution based on the number basis. In Example 1, among the measured Ni powders, a Ni powder having an average particle size of 0.21 μm in the particle size distribution based on the number basis of the area circle equivalent diameter (Heywood diameter) is used.
[0113] [Ceramic powder]
[0114] As the ceramic powder, barium titanate (BaTiO3) powder was used. As with the Ni powder, for each barium titanate powder, the average particle size in the particle size distribution based on the number of area circle equivalent diameters (Heywood diameters) was determined. In Example 1, among the barium titanate powders measured, the barium titanate powder having an average particle size of 0.03 μm in the particle size distribution based on the number of area circle equivalent diameters (Heywood diameters) was used.
[0115] [Ratio of average particle size of ceramic powder to average particle size of conductive powder]
[0116] The ratio of the average particle size of the barium titanate powder to the average particle size of the Ni powder in Example 1 was 0.14.
[0117] [Adhesive]
[0118] As a binder, an organic vehicle prepared by dissolving 10% of ethyl cellulose in 90% of terpineol was used.
[0119] [Manufacturing of cream]
[0120] Using a three-roll mill, Ni powder, barium titanate powder, and a binder were kneaded so that the content of barium titanate powder was 9 mass % relative to the total mass (100 mass %) of the conductive paste composition composed of Ni powder and barium titanate powder, and the total content of Ni powder and barium titanate powder was 55 mass % of the total mass of the conductive paste as a whole, to prepare a conductive paste. At this time, terpineol was added to the insufficient part in the composition so that the amount of ethyl cellulose in the conductive paste was 6 mass %.
[0121] [Surface roughness Ra]
[0122] A conductive paste was applied to a glass substrate by screen printing using a screen printer (manufactured by CWP, 810), and dried at 80°C for 10 minutes. The surface roughness Ra of the obtained dry film was measured using a contact surface roughness meter (manufactured by Tokyo Seimitsu Co., Ltd., 480). It should be noted that the surface roughness Ra was considered acceptable when it was 0.04 μm or less. The surface roughness Ra of the dry film of Example 1 was 0.03 μm.
[0123] [Coverage]
[0124] A screen printer (810 manufactured by CWP) was used to print Ni powder at a density of 0.6 mg / cm 2 The conductive paste is printed on the raw sheet (dielectric sheet) in an amount of 100°C / min under an N2 / H2 environment, and the laminate is fired at 1200°C for 2 hours.
[0125] The fired film was photographed at 3000 times using a scanning electron microscope (SEM) (manufactured by JEOL Ltd., 6360LA), and the area covered by the internal electrode in the photographed area was measured. The coverage was calculated by (area covered by the internal electrode) / (photographed area)×100. It should be noted that a coverage of 75% or more was considered acceptable. The coverage of the fired film of Example 1 was 77%.
[0126] Table 1 shows the properties of the conductive paste composition used in Example 1, the properties of the conductive paste, the surface roughness Ra of the dried film, and the coverage of the fired film.
[0127] [Examples 2 and 3, Comparative Examples 1 to 5]
[0128] A conductive paste, a dried film, and a fired film were obtained in the same manner as in Example 1, and various properties were evaluated, except that any of the average particle size of the Ni powder, the average particle size of the barium titanate powder, the ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder, the content of the barium titanate powder relative to the total mass (100 mass %) of the conductive paste composition, and the content of the conductive paste composition were changed. The results are shown in Table 1.
[0129] Scanning electron microscope images of the fired films obtained in Example 3 (coverage: 79%) and Comparative Example 3 (coverage: 68%) are shown in FIG. Figure 1 and Figure 2 .
[0130]
Claims
1. A conductive paste composition for internal electrodes of a laminated ceramic capacitor, wherein: A conductive powder and a ceramic powder are provided, wherein the average particle size in the particle size distribution based on the number of the conductive powder is greater than or equal to 0.12 μm and less than or equal to 0.3 μm, the average particle size in the particle size distribution based on the number of the conductive powder is the average particle size in the particle size distribution based on the number of area circle equivalent diameters obtained by image processing of images taken with a scanning electron microscope, the ratio of the average particle size in the particle size distribution based on the number of the ceramic powder to the average particle size of the conductive powder is greater than or equal to 0.1 and less than 0.3, the average particle size in the particle size distribution based on the number of the ceramic powder is the average particle size in the particle size distribution based on the number of area circle equivalent diameters obtained by image processing of images taken with a scanning electron microscope, the average particle size of the ceramic powder is greater than or equal to 0.02 μm and less than or equal to 0.07 μm, and the content of the ceramic powder is greater than or equal to 5.5% by mass and less than or equal to 13% by mass relative to the total mass of the conductive powder and the ceramic powder.
2. The conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to claim 1, wherein A ratio of the average particle size of the ceramic powder to the average particle size of the conductive powder is 0.15 or more and 0.25 or less.
3. The conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to claim 1, wherein The average particle size of the conductive powder is 0.15 μm or more and 0.25 μm or less.
4. The conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to claim 1, wherein The average particle size of the ceramic powder is 0.03 μm or more and 0.05 μm or less.
5. The conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to claim 1, wherein The conductive powder is at least one metal powder selected from Ni, Pd, Pt, Au, Ag, Cu and alloys thereof.
6. The conductive paste composition for internal electrodes of a multilayer ceramic capacitor according to claim 1, wherein The ceramic powder is composed of ceramic powder containing perovskite-type oxide as a main component.
7. A conductive paste for internal electrodes of a laminated ceramic capacitor, wherein: The present invention is a conductive paste having a conductive paste composition and an adhesive. The conductive paste composition is composed of the conductive paste composition according to claim 1, The content of the conductive paste composition is 40 mass % or more and 60 mass % or less relative to the total mass of the conductive paste.
8. A method for producing a conductive paste composition, wherein: include: A process for preparing conductive powder; A process for preparing ceramic powder; A step of dispersing the ceramic powder; as well as The conductive powder is mixed with the ceramic powder after the dispersion treatment and the dispersion treatment is carried out. In the step of preparing the conductive powder, a conductive powder having an average particle size of 0.12 μm or more and 0.3 μm or less in a particle size distribution based on the number of area circle equivalent diameters obtained by image processing of an image taken with a scanning electron microscope is selected; In the step of preparing the ceramic powder, a ceramic powder is selected in which the ratio of the average particle size in the particle size distribution based on the number of area circle equivalent diameters obtained by image processing of an image taken with a scanning electron microscope to the average particle size of the conductive powder is 0.1 or more and less than 0.3, In the step of mixing and dispersing the conductive powder and the ceramic powder after the dispersion treatment, the content of the ceramic powder is 5.5 mass % or more and 13 mass % or less relative to the total mass of the conductive powder and the ceramic powder.
Citation Information
Patent Citations
Electrode pasge for porcelain capacitor
JP1982030308A
Conductive paste for multilayer ceramic electronic paste, manufacturing method of multilayer ceramic electronic paste by use thereof, and multilayer ceramic capacitor
JP2016033962A
Conductive paste, and dried film and laminated ceramic capacitor using conductive paste
JP2010087434A